Protocol of the Development of a Core Outcome Set for Ischemic Stroke in Clinical Trials of Chinese Medicine. (5th October 2020) - Xie, Qianwen; Deng, Xueyi; Xiao, Jingmin; Chen, Xueyin; He, Yihan; Yang, Lihong; Liu, Shaonan; Lai, Jiaqi; Cai, Yefeng; Sun, Jingbo; Guo, Xinfeng
Abstract : Background . Ischemic stroke (IS) seriously impacts the quality of life of survivors. Chinese medicine (CM) has been developed for more than 2000 years and plays a key role in the treatment of ischemic stroke. Many Chinese medicine clinical trials have been conducted; however, the heterogeneity of outcome measurements and reporting limits implications of the findings in clinical practice and health policy development. Therefore, it is important to develop a core outcome set (COS) that should be used and reported in trials for ischemic stroke treated by Chinese medicine. This protocol describes the process of developing the IS-CM-COS. Methods and Analysis . The development of the COS will involve the following four steps: (1) A list of outcomes reported in the registered and published Chinese medicine trials of ischemic stroke will be extracted by conducting a systematic literature review. (2) An additional outcome list will be collected by semistructured interview to patients with ischemic stroke. (3) A two-round Delphi survey will be performed to prioritize and condense the outcomes. (4) In the consensus meeting, a final recommended COS will be developed. Discussion . The COS could improve the reliability and consistency of outcome reporting. We hope that this IS-CM-COS will be used in the future Chinese medicine trials for the treatment of ischemic stroke and improve research quality. Trial Registration . This study was registered with the Core Outcome Measures in Effectiveness Trials Initiative (http://www.comet-initiative.org/studies/details/1282 ).